A high-throughput strategy for screening umami peptides from Chouguiyu based on peptidomics and machine learning-assisted molecular simulation - Sitong Lyu; Shichao Xuan; Fan Yang; Honglin Yu; Di Meng; Jianqing Zhou; Cristabelle De Souza; Zhe Zhang; Tongjie Liu; Huaxi Yi; Qingjuan Tang; Lanwei Zhang; et al. (Food Research International, 2026)

Protein and polyphenol structure transformation persuade “colloid-suspension” phase conversion in green tea beverages - Xinxin Wang; Lin Wang; Yunqing Liu; Yani Pan; Xinyu Feng; Wenzhi Ling; Xiangru Wang; Sitong Zhong; Yili Shen; Ranran Zhao; Yuefei Wang; Ping Chen; et al. (Food Chemistry, 2026)

Quintuple-stimulus responsive Ti3C2Tx-silk nanofiber@Fe3O4/polymer bilayer actuators for programmable soft robotics and non-contact intelligent transportation - Kaihuai Yang; Zhen Wang; Junjie Lin; Wanling Cai; Sitong Zeng; Peidi Zhou; Mingcen Weng (Chemical Engineering Journal, 2026)

Integrated multi-omics and machine learning reveal aroma profiles and brand fingerprints in various fermented mandarin fish - Jian Shi; Shichao Xuan; Sitong Lyu; Fengzhi Qiao; Qingjuan Tang; Naiyong Xiao; Mingyu Yin; Wenzheng Shi; Lanwei Zhang; Jianan Sun; Yongxiang Wu; Kai Lin (Food Bioscience, 2026)

Exogenous phospholipid intermediates mediate membrane lipid composition remodeling to enhance spray-drying survival of Lactobacillus bulgaricus - Fengzhi Qiao; Meijun Liu; Wenhao Ding; Sitong Lyu; Zhe Zhang; Tongjie Liu; Huaxi Yi; Lanwei Zhang; Kai Lin (Food Bioscience, 2026)

The formation of autophagosomes in the development process of rice endosperm is affected by endogenous ascorbic acid - Le Yu; Mengwei Chen; Haoran Yan; Zeliang Ouyang; Xinyu Liu; Sitong Lin; Yixuan Tang; Zhipeng Xu; Chunyu Liu; Peiyi Chen; Liping Zhou; Yonghai Liu (Acta Physiologiae Plantarum, 2026)

Astaxanthin-rich Haematococcus pluvialis mitigates oxidative damage and restores gel functionality in myofibrillar protein for enhanced meat product quality - Ziyuan Zhang; Lin Wang; Mengning Zhao; Taotao Li; Sitong Liu; Jiayu Xu; Qian Liu; Chuanai Cao; Baohua Kong; Xiufang Xia; Fangda Sun (Food Chemistry, 2025)

Photothermal actuator based on Nb4C3Tx@CNF composite for bionic applications and wireless cargo transportation - Sitong Zeng; Zhen Wang; Junjie Lin; Nuozhou Yi; Peidi Zhou; Qiaohang Guo; Mingcen Weng; Kaihuai Yang (Chemical Engineering Journal, 2025)

Bclaf1 mediates super-enhancer-driven activation of POLR2A to enhance chromatin accessibility in nitrosamine-induced esophageal carcinogenesis - Xiangjun Zhou; Xueqiong Zhou; Jun Li; Yingzheng He; Shizhen Qiu; Ye Xu; Zeyu Liu; Yina Yao; Jia Liu; Ying Wen; Sitong Xie; Jialong Chen; et al. (Journal of Hazardous Materials, 2025)

Exploring exhaled volatile organic compounds as potential biomarkers in anti-MDA5 antibody-positive interstitial lung disease - Yuxuan Wang; Xuewen Wang; Luqin Yang; Ke Wang; Fengqin Zhang; Huihui Yue; Junqi Wang; Minhua Peng; Pengnan Fan; Xiangcheng Qiu; Han Zhang; Wei Lin; et al. (Molecular and Cellular Biochemistry, 2025)

Taurine supplementation alleviates asthma airway inflammation aggravated by HOCl exposure - Yingjun Chen; Shiting Yi; Qian Wang; Yanwen Li; Sitong Lin; Shixiu Liang (Journal of Hazardous Materials, 2025)

The potential of golden apple snail (Pomacea canaliculata) meat meal as an alternative protein source for juvenile Chinese mitten crab (Eriocheir sinensis) - Wenxiang Yao; Chunyan Zhang; Rui Jia; Sitong Zhao; Weibo Jiang; Guoan Hua; Sizhe Zhao; Apeng Lin; Jianguo Wang; Quan Wang (Frontiers in Marine Science, 2025)
This study investigated the effects of replacing dietary fish meal (FM) with golden apple snail ( Pomacea canaliculata ) meat meal (PCM) on growth performance, non-specific immunity and intestinal health of juvenile Chinese mitten crab ( Eriocheir sinensis ). Four hundred juvenile Chinese mitten crabs (2.39 ± 0.03) g were randomly distributed into five groups in quadruplicate (20 crabs per tank), and each group was fed with diets that replaced FM with PCM at 0% (FM-20, containing 200 g/kg FM), 25% (FM-15), 50% (FM-10), 75% (FM-5), and 100% (FM-0) for 8 weeks, respectively. The results showed that the growth, whole body composition, digestive enzyme activities, antioxidant performance, non-specific immunity, intestinal histology and microbiota composition of FM-15 and FM-10 groups all reached the same level as the FM-20 group ( P > 0.05). While the replacement ratio reached 75%, the FCR was significantly increased and the peritrophic membrane thickness was significantly decreased ( P< 0.05). When 100% FM was replaced, significantly decreased the growth performance, serum antioxidant and immune enzyme activities, mid-intestine folds height, width and the peritrophic membrane thickness ( P< 0.05), and significantly increased the abundance of intestinal harmful bacteria Vibrio ( P< 0.05). In conclusion, PCM can effectively replace 50% dietary FM (100 g/kg) without negative effects on the growth performance, intestinal health, serum immune, and antioxidant indexes of juvenile E. sinensis .

Identification and characterization of GRAS genes in passion fruit (Passiflora edulis Sims) revealed their roles in development regulation and stress response - Xinkai Cai; Denglin Li; Chaojia Liu; Jiayi Chen; Xiuqing Wei; Sitong Hu; Lin Lu; Shengzhen Chen; Qinglong Yao; Shiyu Xie; Xiaowen Xu; Ruoyu Liu; et al. (Plant Cell Reports, 2025)

Transesterification of acidic palm oil using solid waste/CaO as a bifunctional catalyst - Jisen Liu; Tong Lin; Shengli Niu; Jie Zhu; Zihao Yang; Jie Geng; Sitong Liu; Yue Zheng; Bo Liang; Xiaobin Sun; Huaji Zhang (Fuel, 2024)